Accessing Shared Culture for Conflict Transformation The Arts of Pattani - Kvam, Hilde (Journal of Urban Culture Research, 2015)
Since 2004 antagonism between the Malay-Muslim population in the South of Thailand and ethnic Thai-Buddhist groups has escalated. The effect has been increasing acts of violence, rebellions and state of emergency. The antagonism between the two ethnic groups has been most pronounced in the Pattani region where Islam is identified as a non-Thai culture. Throughout centuries this region has been populated with peoples holding diverse religions, customs and cultural traditions who until modern times have coexisted relatively peacefully, inspired and enriched each other. In this area, arts and culture among Malays and Thais have shared roots with artistic forms and expressions that are very much alike. The author will focus upon the cultural similarities of the two ethnic groups on the border of Malaysia and Thailand. Will mobilizing the common local culture act as a vehicle for increased understanding and reconciliation between the two ethnic groups?